Enhancing Toughness and Impact Strength of Epoxy Resins by Using Hyperbranched Polymers - Hangyu Park; Youngson Choe (International Journal of Polymer Science)
Toughened epoxy has been widely used in industrial areas such as automotive and electronics. In this study, nanosized hyperbranched polymers (HBPs) as a flexibilizer are synthesized and embedded into epoxy resin to enhance the toughness and flexibility. Two different HBPs, hyperbranched poly(methylacrylate-diethanolamine) (poly(MA-DEA)) and poly(methylacrylate- ethanolamine) (poly(MA-EA)), were prepared and blended with both epoxy and polyetheramine, a curing agent. The molecular size of HBPs was estimated to be 6 ~ 14 nm in diameter. The molecular weight of HBPs ranges from 1500(1.5 K) to 7000(7.0 K) g/mol. In cured epoxy/HBP blends, no phase separations are occurred, indicating that HBPs possess sufficient miscibility with epoxy. The tensile toughness of the blends increased with changing the molecular weight of HBPs without sacrificing tensile strengths. The impact strength of the blends increases stiffly until the loading % of HBPs in the blends reaches 10 wt%. In addition, the experimental studies showed that impact resistance also increased with an increase in molecular weight of HBPs. The obtained impact resistance of the epoxy/HBP blends with 10 wt% was 270% more effective compared to that of cured neat epoxy.